[PP.10.13] FREQUENT EXACERBATIONS OF CHRONIC OBSTRUCTIVE PULMONARY DISEASE AND ATHEROSCLEROSIS: WHAT RELATIONSHIP?. (September 2017) - Namitokov, A.; Kosmacheva, H.; Zafiraki, V.; Porhanov, V.
Abstract : Objective: To determine angiographic features of coronary atherosclerosis in patients with frequent COPD exacerbations Design and method: There was 110 patients with acute coronary syndrome and COPD included in observation, 24 of which (study group) had frequent COPD exacerbations (FE). Selection criteria were: COPD diagnosis; age >=40 years; smoking history >=10 pack-years; acute coronary syndrome at the presentation to hospital; >=1 stent implantation; >= COPD exacerbations during last year, diagnosed accordingly to GOLD criteria. Control group had <2 COPD exacerbations per last year, other including criteria were the same. Detail «segment by segment» analysis was used to describe all lesions. >= 50% lesions were considered as major, and <50% as minor. We also monitored long-term outcomes of PCI Results: Follow-up median consist 19 months. There was no significant difference between the groups in regards of age, gender, cholesterol levels, myocardial infarction history, left ventricular ejection fraction, as well as arterial hypertension, diabetic mellitus, chronic kidneys disease.We have found more severe atherosclerotic lesions in group with FE of COPD. The row of features in atherosclerotic lesion distribution and frequency were founded: 1) patient with FE of COPD had higher total number of lesions, major lesions in main arteries and total occlusions in main and collateral arteries; 2) there was no statistically significant differences in frequency of total lesion number in left main artery, proximal, medium and distal segments in both groups, however the number of proximal and distal major lesions was significantly higher in group with FE of COPD; 4) extended (>20 mm) stenosis (no depends of localisation) are more specific for the patients with FE of COPD. The frequency of occurrence of cardiac events such as cardiac death, myocardial infarction, stroke, coronary artery bypass grafting did not differ individually. However, the frequency of MACE the differences were statistically significant (2.31 (95% CI 1, 45–3, 68). Conclusions: COPD with FE determines a high risk of major cardiovascular and earlier their onset in the late period after PCI